Determinants of Firm Value in the Transportation and Logistics Sector: The Roles of Capital Structure, Dividend Policy, Profitability, and Firm Size - Lukman Hakim; Indriyati Wijaya (Journal of Managerial Sciences and Studies, 2026)
The primary objective of a company is to maximize firm value in order to enhance shareholder wealth. Firm value serves as an important indicator of corporate performance and reflects investors’ perceptions regarding a company’s future prospects. This study aims to examine the effects of capital structure, dividend policy, profitability, and firm size on firm value among transportation and logistics companies listed on the Indonesia Stock Exchange (IDX). The study adopts a quantitative explanatory approach using secondary data obtained from annual financial statements. The population consists of 42 transportation and logistics companies listed on the IDX during the 2021–2024 period. Using purposive sampling, 10 companies were selected as the research sample, resulting in 40 firm-year observations. Data were analyzed using multiple linear regression with the assistance of Statistical Package for the Social Sciences (SPSS). Prior to hypothesis testing, classical assumption tests comprising normality, multicollinearity, heteroscedasticity, and autocorrelation tests were conducted. The results reveal that capital structure, profitability, and firm size have positive and significant effects on firm value. In contrast, dividend policy does not significantly affect firm value. These findings support Signaling Theory, indicating that profitability, capital structure, and firm size function as relevant financial signals that are positively interpreted by investors, thereby enhancing firm value. Meanwhile, dividend policy is not consistently perceived as an effective signal by the market. The study implies that managers should prioritize improving profitability, maintaining an optimal capital structure, and strengthening company scale to increase firm value and investor confidence.